Exigências de energia, proteína, cálcio e fósforo para mantença e ganho de cordeiros corriedale - Martins, Andressa Ana (2017)
This project aims to determine the body composition and to estimate the nutritional requirements of energy, protein, calcium and phosphorus for maintenance and weight gain of Corriedale lambs. The experiment was carried out at the Sheep Laboratory of the Universidade Federal de Santa Maria. The total of 42 Corriedale male lambs were castrated, weaned at 50 days of age and confined in individual stalls (2 m²). The diet was composed of sorghum silage (Sorghum bicolor (L) Moench), corn grain (Zea mays L.), soybean meal (Glycine max L.) and mineral mixture, being calculated to meet the requirements of crude protein, metabolizable energy and macrominerals recommended by the NRC (2007), to gain 0.200 kg daily. After 14 days to adapt the animals to the experimental conditions, six lambs were randomly drawn and slaughtered. Among the remaining, 24 animals were fed ad libitum and slaughtered at 28, 33 or 38 kg of live weight (PV), and 12 animals were submitted to two levels of food supply (70 and 55% of consumption ad libitum). The slaughter of the latter was carried out together with those fed ad libitum and slaughtered at 38 kg of BW. Eight groups of the body components were constituted, 1: internal organs; 2: treatment; 3: internal fat; 4: blood; 5: edible portion; 6: skin; 7: wool and 8: small portions of bones, which, after grinding in an electric meat grinder, 0.5 kg samples were stored for further laboratory analysis. In these samples the body contents of nitrogen, fat, energy, calcium and phosphorus were determined. These data were submitted to regression analysis. The remaining six lambs were submitted to a digestibility test, under a 3x3 Latin Quadrado, with the objective of evaluating the nutritional value of the diet under the different levels of consumption. Daily samples were collected in the collection period, leftovers, faeces and urine, these composed by animal and stored for later laboratory analysis. Body composition ranged from 204.05 to 208.23 g protein, 101.17 to 175.72 g fat and 2106.8 to 2826.21 kcal energy per kg body weight (EBW). The requirement of maintenance net energy, represented by fasting heat production, was 61.65 kcal/kg EBW0.75. The requirements of metabolizable energy for gain were between 409 and 1105 kcal/day for lambs from 28 to 38 kg of BW. The endogenous nitrogen excretion was 279.9 mg/kg BW0.75/day, which corresponded to the requirement of liquid protein for maintenance of 1.75 g/kg BW0.75/day. The requirements of metabolizable protein for weight gain of lambs with 28 and 38 kg of BW and average daily gain of 250 g were 43,35 and 38,75 g/day. Body composition ranged from 16.83 to 16.49 g of calcium and 4.69 to 4.64 g of phosphorus per kg of EBW. The net maintenance requirements for animals between 28 and 38 kg live weight were 450 mg Ca/day and 329 mg P/day. Dietary requirements were from 7.05 to 6.93 g/day of calcium and 4.14 to 4.11 g/day of phosphorus for Corriedale lambs, from 28 to 38 kg of BW, gaining 200 g/day.